Facile One-Pot Transformation of Primary Alcohols into 3-Aryl- and 3-Alkyl-isoxazoles and -pyrazoles - Kobayashi, Eiji; Togo, Hideo (Synthesis, 2019)
Various primary alcohols were smoothly transformed into 3-aryl- and 3-alkylisoxazoles in good yields in one pot by successive treatment with PhI(OAc)2 in the presence of TEMPO, NH2OH, and then NCS, followed by reaction with alkynes in the presence of Et3N. Similarly, various primary alcohols were smoothly transformed into 3-aryl- and 3-alkylpyrazoles in good yields in one pot by successive treatment with PhI(OAc)2 in the presence of TEMPO, PhNHNH2, and then NCS and decyl methyl sulfide, followed by reaction with alkynes in the presence of Et3N. Thus, both 3-aryl- and 3-alkylisoxazoles, and 3-aryl- and 3-alkylpyrazoles could be prepared from readily available primary alcohols in one pot under transition-metal-free conditions.
Keywords: isoxazole; pyrazole; alcohol; oxime; hydrazone; cycloaddition